Comodulation of Dengue and Chikungunya Virus Infection During a Coinfection Scenario in Human Cell Lines - Taraphdar, Debjani; Singh, Bharati; Pattanayak, Sabyasachi; Kiran, Avula; Kokavalla, Poornima; Alam, Mohd. Faraz; Syed, Gulam Hussain (Frontiers in Cellular and Infection Microbiology, 2022)
The Dengue virus (DENV) and Chikungunya virus (CHIKV) are the arboviruses that pose a threat to global public health. Coinfection and antibody-dependent enhancement are major areas of concern during DENV and CHIKV infections, which can alter the clinical severity. Acute hepatic illness is a common manifestation and major sign of disease severity upon infection with either dengue or chikungunya. Hence, in this study, we characterized the coexistence and interaction between both the viruses in human hepatic (Huh7) cells during the coinfection/superinfection scenario. We observed that prior presence of or subsequent superinfection with DENV enhanced CHIKV replication. However, prior CHIKV infection negatively affected DENV. In comparison to monoinfection, coinfection with both DENV and CHIKV resulted in lower infectivity as compared to monoinfections with modest suppression of CHIKV but dramatic suppression of DENV replication. Subsequent investigations revealed that subneutralizing levels of DENV or CHIKV anti-sera can respectively promote the ADE of CHIKV or DENV infection in FcγRII bearing human myelogenous leukemia cell line K562. Our observations suggest that CHIKV has a fitness advantage over DENV in hepatic cells and prior DENV infection may enhance CHIKV disease severity if the patient subsequently contracts CHIKV. This study highlights the natural possibility of dengue–chikungunya coinfection and their subsequent modulation in human hepatic cells. These observations have important implications in regions where both viruses are prevalent and calls for proper management of DENV-CHIKV coinfected patients.